Challenges, Opportunities, and Motivations of Students in Studying Food Technology Towards the Enhancement Program - Rana, Herbert Puhawan (Jayapangus Press, 2024)
Opportunities, challenges, and motivation offer flexibility in developing the enhancement program. This be taken into consideration to address any gaps in the knowledge of the many aspects of food technology studies. Using a phenomenological method, the researcher explored the experiences and beliefs of the participants which was consists of eight (8) undergraduates students studying food technology. Purposive sampling was used to choose the participants. Codes and themes were used in the stud where Focus Group Discussion (FGD) were utilized to acquire responses and gather information. Based on the results of the study, three themes emerged concerning the challenges and opportunities: sustainability issues, technology advances and innovation and product development. Meanwhile, in motivation of the students, the results emphasized the innovation and product development which implies that creativity and innovation must adapt to the ever-changing learning. With an emphasis on the impact on student motivation and the need for adaptable instructional strategies, the study seems to highlight the connections among sustainability, technology, innovation, and the development of products. Thus, implementing comprehensive training intended to reaffirm the institution's commitment to improve the knowledge and skills of food technology students. The enhancement program offers the advancement and capability program in the Food Technology institutions that strive to offer excellent instruction ought to give food technology sector significant thought and support into real-life situations. This suggests that institution should concentrate on developing and improving their knowledge, abilities, and skills in the area of food technology.